Supernatural. Season eight [videorecording (DVD)] - Kripke, Eric (Supernatural (Television program), 2013)
The Leviathan threat has ended but Dean's miraculous return from Purgatory unsettles his relationship with his brother, especially his friendship with fellow escapee and vampire Benny. Sam is haunted by his 'last-chance' romance with a woman where he finally found something of a normal life. Both Winchesters face shattering choices along with their best chance to strike a deathblow to evil. A Divine Tablet reveals the means to closing the Gates of Hell forever, but the cost may be cataclysmic to them and their angelic ally Castiel. Full of demons, witches, vampires, titans, a fairy, a hellhound, a golem and a toontown terror trip, season eight is Sam and Dean's more horrific journey yet.